First-in-human study of 99mTc-labeled fucoidan, a SPECT tracer targeting P-selectin - Reindert F. Oostveen; Kang H. Zheng; Yannick Kaiser; Nick S. Nurmohamed; Jeffrey Kroon; Tim C. de Wit; Edwin Poel; Joel Aerts; Francois Rouzet; Erik S. G. Stroes; Didier Letourneur; Hein J. Verberne; et al. (EJNMMI Research)
Abstract Background Activation of endothelial cells and platelets in atherothrombosis is characterized by upregulation of P-selectin. As a consequence, P-selectin represents a potential target for molecular imaging to identify thrombosis at an early stage. Fucoidan is a polysaccharide ligand extracted from brown algae with nanomolar affinity for P-selectin. This first-in-human study evaluated in healthy volunteers the safety, whole-body biodistribution, and dosimetry of 99mTc-fucoidan (Good Manufacturing Practices grade). We also investigated whether we could observe binding of 99mTc-fucoidan to human thrombi ex vivo and in vivo. In ten healthy volunteers, conjugate whole-body scans were performed up to 24 h following intravenous injection of 99mTc-fucoidan (370 MBq). Moreover, 99mTc-fucoidan uptake in ex vivo human thrombi (n = 11) was measured by gamma counting. Additionally, three patients with a newly diagnosed deep vein thrombosis (DVT) were subjected to 99mTc-fucoidan SPECT/CT imaging. Results 99mTc-fucoidan was well tolerated in all participants without any drug-related adverse events. The total-body absorbed dose in males was comparable to females (0.012 ± 0.004 vs. 0.011 ± 0.005 mSv/MBq; p = 0.97). Gamma counting experiments demonstrated binding of tracer to ex vivo human thrombi that was 16% lower after blocking with a natural P-selectin ligand, Sialyl Lewis X. 99mTc-fucoidan demonstrated specific uptake at the thrombus site in one out of three scanned patients with DVT. Conclusions 99mTc-Fucoidan has a favorable biodistribution and safety profile. 99mTc-fucoidan exhibited specific binding to human thrombi in both in vivo and ex vivo settings. Nonetheless, the in vivo results do not support further clinical investigation of 99mTc-fucoidan as an imaging modality for DVT. Other clinical implementations of a technetium− 99m-labeled P-selectin tracer should be considered. Trial registration: Clinicaltrials,NCT03422055.Registered 01/15/2018. URL: https://clinicaltrials.gov/study/NCT03422055 Landelijk Trial Register, NL7739. Registered 4/2/2019 . https://onderzoekmetmensen.nl/en/trial/26785